Histone deacetylase-6 modulates Tau function in Alzheimer's disease - Qureshi, Tazeen; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-Molecular Cell Research, 2022)
Alzheimer's disease (AD), one of the major tauopathies, is multifactorial with a massive demand for disease modifying treatments rather than symptom management. An AD-affected neuron shows Tau depositions generated due to overload on the proteostasis machinery of the cell and/or abnormal post-translational modifications on Tau protein. Loss of memory or dementia is the most significant concern in AD, occurring due to the loss of neurons and the connections between them. In a healthy brain, neurons interact with the environment and each other through extensions and migratory structures. It can thus be safe to assume that Tau depositions affect these growth structures in neurons. A Histone Deacetylase, HDAC6, has shown elevated levels in AD while also demonstrating direct interaction with the Tau protein. HDAC6 interacts with multiple proteins in the cell and is possibly involved in various signalling pathways. Its deacetylase activity has been a point of controversy in AD; however other functional domains remain unexplored. This review highlights the beneficial potential of HDAC6 in AD in mediating both Tau proteostasis and cytoskeletal rewiring for the neuritic extensions through its Ubiquitin Binding domain (HDAC6 ZnF UBP).
Keywords: Actin; Cytoskeleton; HDAC6; Microtubules; Proteostasis; Tau; ZnF UBP domain